Comuinicación externa de los proyectos culturales del Instituto Societá Dante Alighieri para la gestión de su imagen - Tobar Álvarez, Constanza Daniela (2016)
This Project was developed with the aim to create a communicational proposal for the Institute Società Dante Alighieri of Quito-Ecuador. The main objective was to project the institute’s image linked to their cultural management, using as a basis their cultural projects. Such cultural projects are a core component of the identity of the institute. Cultural management is an area that has been neglected in the country. Therefore, cultural organizations have turned this fact into an advantage, by creating a strong image of the organization in order to become an outstanding referent among its different audiences. The Institute Società Dante Alighieri seeks to promote and broadcast Italian culture in Ecuador, because it is part of its identity and the audiences should perceive it as a culture promoter and not only as a language institute. This Project displays and proposes several strategies and structured actions, based on the corporate philosophy and identity, seeking to align the essence of the organization to the released messages, thus, engaging the institute’s strategic stakeholders to develop the institute’s communication management, with the purpose of projecting the desired image.